Learning outcomes : constructing a bridge between professional accreditation and higher education quality assurance requirements in health : extension report. - O'Keefe, Maree; Henderson, Amanda; Chick, Rebecca (Office for Learning and Teaching, 2015)
The outcomes of the ALTC Learning and Teaching Academic Standards project reinforced the importance of ensuring ongoing alignment between threshold learning outcomes and professional accreditation standards. This is a report from an extension project which built on and disseminated outcomes from the project, Harmonising higher education and professional quality assurance processes for the assessment of learning outcomes in health, which was completed in 2013. This report documents the dissemination activities that were undertaken, outcomes achieved and consider some future directions. Project activities primarily related to the demonstration disciplines identified for the Harmonising project (dentistry, medicine, midwifery, nursing and physiotherapy).